Immunohistochemical changes of maxillary sinus mucosa with underlying adenomatous polyposis - Kovalenko, I. S.; Коваленко, Iнна Сергiївна (Zaporozhye state medical university, 2017)
Introduction. In maxillary sinusitis pathogenesis researchers paid much attention to the role of paranasal sinuses, sinus drainage dysfunctions, mucocyliary transport system disorders in cases of damage of sinuses mucous membranes. Pathohistological, im¬munohistochemical and morphometric studies of mucosa were conducted. However, to evaluate the local inflammatory response in cases of chronic sinusitis and improvement of individual therapy for the patients, the immunohistochemical studies of the com¬position of inflammatory immunocyte infiltrates of paranasal sinus mucosa and adenoid vegetations bioptate would be reasonable. The aim of the research was to study the immunohistochemical content of immunocyte infiltrates of paranasal sinuses ade¬nomatous polyps in biopsy samples of patients suffering from chronic sinusitis. Materials and Methods. Paranasal sinuses adenomatous polyps removed during surgery of 22 patients suffering from chronic maxillary sinusitis were studied. Immunohistochemical studies of paraffin sections of the removed polyps were performed using appropriate primary antibodies and visualization systems DAKO EnVision+ System (DAKO, Denmark). Results. During microscopic investigation of paranasal sinuses adenomatous polyps of the patients suffering from chronic sinusitis, moderate and severe immunocyte infiltration of polyp stroma sometimes with focal follicular structures was presented. Immunohistochemical investigation of the cellular composition of these infiltrates proved the presence of CD8+ T-killer cells, CD4+ T-helper cells, CD68+ macrophages as well as single plasma cells. The irregularity of these cells markers expression was determined in dependence of the severity of inflammatory cell infiltration. Conclusions. In the patients with chronic maxillary polyp sinusitis with mild and moderate immunocyte infiltration of paranasal sinus mucosa, among immune cells the CD4+ T-lymphocytes occupied the most relative area in polyp stroma, plasma cells – the least (р < 0.001). In the patients with significant immunocellular infiltration in immunocyte follicular infiltration of polyp stroma the relative area of CD4+ and CD8+ T-lymphocytes significantly exceeded the relative area of macrophages and plasma cells. У патогенезі верхньощелепних синуситів досі найбільшу увагу дослідники приділяли ролі співусть приносових пазух, порушенню їхньої дренажної функції, зменшенню дієздатності мукоциліарної транспортної системи при ураженні слизової оболонки синусів. Для цього застосовувалися патогістологічні, імуногістохімічні та морфометричні дослідження слизової оболонки. Однак для сучасного оцінювання місцевої запальної реакції під час хронічних синуситів та уточнення персоніфікованої терапії хворих доцільними є імуногістохімічні дослідження складу запальних та імуноклітинних інфільтратів біоптатів слизової оболонки приносових пазух та аденоїдних вегетацій. Мета роботи – імуногістохімічне визначення клітинного складу імуноцитарних інфільтратів аденоматозних поліпів придаткових пазух носа в біопсійно-операційному матеріалі хворих на хронічний синусит. Матеріали та методи. Досліджено аденоматозні поліпи придаткових пазух носа, що вилучені під час операції у 22 хворих на хронічний верхньощелепний синусит. У парафінових зрізах видалених поліпів виконувались імуногістохімічні дослідження з використанням відповідних первинних антитіл і системи візуалізації DAKO EnVision+ System («DAKO», Данія). Результати. Під час мікроскопічного дослідження аденоматозних поліпів придаткових пазух носа хворих на хронічний синусит виявлена помірна та виразна імуноцитарна інфільтрація строми поліпів, іноді – з формуванням вогнищевих фолікулоподібних структур. Імуногістохімічний аналіз клітинного складу таких інфільтратів показав наявність у них CD8+ Т-кілерів, CD4+ Т-хелперів, CD68+ макрофагів, а також поодиноких плазматичних клітин. Встановлена нерівномірність експресії маркерів цих клітин залежно від виразності запально-клітинної інфільтрації. Висновки. У хворих на хронічний верхньощелепний поліпозний синусит зі слабкою та помірною імуноцитарною інфільтрацією слизової оболонки придаткових пазух у стромі поліпів серед імуноцитів найбільшу відносну площу займали CD4+ Т-лімфоцити, найменшу – плазматичні клітини (р < 0,001). У пацієнтів із виразною імуноклітинною інфільтрацією в імуноцитарних фолікулоподібних інфільтратах строми поліпів відносна площа CD4+ та CD8+ Т-лімфоцитів статистично значуще перевищувала відносну площу макрофагів і плазматичних клітин.
Імуногістохімічні зміни слизової оболонки верхньощелепного синуса при аденоматозному поліпозі
Keywords: maxillary sinusitis; adenomatous polyp; subpopulation of T-lymphocytes; macrophages; plasma cells; верхньощелепний синусит; аденоматозний поліп; субпопуляції Т-лімфоцитів; макрофаги; плазматичні клітини